2012
DOI: 10.1051/0004-6361/201118528
|View full text |Cite
|
Sign up to set email alerts
|

Young stars inϵChamaleontis and their disks: disk evolution in sparse associations

Abstract: Context. The nearby young stellar association Cha has an estimated age of 3-5 Myr, making it an ideal laboratory to study the disk dissipation process and provide empirical constraints on the timescale of planet formation. Aims. We wish to complement existing optical and near-infrared data of the Cha association, which provide the stellar properties of its members, with mid-infrared data that probe the presence, geometry, and mineralogical composition of protoplanetary disks around individual stars. Methods. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 107 publications
(167 reference statements)
8
50
0
Order By: Relevance
“…Its SED shows the strong infrared excess emission (see the right panel in Figure 12), suggesting that it is surrounded by a disk. Similar young stars have been discovered in our previous spectroscopic surveys in Orion (Fang et al 2009(Fang et al , 2013a, and also found in other regions, e.g., the Lupus 3 dark cloud, Taurus, and òCha White & Hillenbrand 2004;Fang et al 2013b). One promising hypothesis for these exotic objects is that they are harboring disks with high inclinations, and the light seen mainly comes from photons scattered off the disk surfaceand is therefore much reduced.…”
Section: Disk Properties 431 a Subluminous Objectsupporting
confidence: 90%
“…Its SED shows the strong infrared excess emission (see the right panel in Figure 12), suggesting that it is surrounded by a disk. Similar young stars have been discovered in our previous spectroscopic surveys in Orion (Fang et al 2009(Fang et al , 2013a, and also found in other regions, e.g., the Lupus 3 dark cloud, Taurus, and òCha White & Hillenbrand 2004;Fang et al 2013b). One promising hypothesis for these exotic objects is that they are harboring disks with high inclinations, and the light seen mainly comes from photons scattered off the disk surfaceand is therefore much reduced.…”
Section: Disk Properties 431 a Subluminous Objectsupporting
confidence: 90%
“…Since we are well below the self-gravitating limit the mass effectively becomes a scaling factor and does not affect the hydrodynamics. SED models of HD 104237 are consistent with a nonflaring disc (Fang et al 2013;Hales et al 2014), while our equation of state enforces a flared disc. The flaring is not strong, and H/R only goes from 0.03 at the inner edge to 0.07 at the outer edge of our disc, so we do not expect this to affect the results of our simulations.…”
Section: Simulationsmentioning
confidence: 67%
“…Therefore, the interaction between disks and companions has been proposed as an efficient mechanism to dissipate disks (Lin & Papaloizou 1993). Observationally, this mechanism can be very efficient in disk disperal at very early stages (<1 Myr, Cieza et al 2009;) and may play a key role in dissipating the Table 4 is available in electronic form at http://www.aanda.org disks in sparse stellar associations (Bouwman et al 2006;Fang et al 2013b).…”
Section: Introductionmentioning
confidence: 99%